Youth participatory research evidence to inform health policy: a systematic review protocol. Issue 8 (11th August 2020) - Njelesani, Janet; Hunleth, Jean
Abstract : Introduction: Young people's participation in health research produces knowledge that is indispensable for creating appropriate and effective policies. However, how best to disseminate youth participatory research evidence to impact health policy is not known. Therefore, the objectives of this systematic review are to describe the evidence produced through youth participatory research, including the strategies used to disseminate youth participatory research evidence to health policymakers. These are necessary to improve policymakers' use of youth participatory research evidence and, thereby, make programmes more impactful for young people. Methods and analysis: The meta-narrative methodology will guide the systematic review to highlight the contrasting and complementary evidence on the use of engaging youth in research to affect health policymaking. Relevant studies will be identified by searching electronic databases, including but not limited to EBSCO, PROQUEST, OVID Medline, Sociological Abstracts and Google Scholar from inception to December 2020. The methodological quality of included quantitative, qualitative and mixed-methods research studies will be assessed using valid appraisal tools. The meta-narrative approach to analysis will include identifying meta-narratives of how youth participation informed the health research findings. Ethics and dissemination: An advisory group of young people will advise on the study and dissemination of the findings. As part of our plan for active dissemination, we will produce a policy brief that builds the rationale for using research with and by youth as part of an evidence base necessary for achieving youth health outcomes.